Fear of Sudden Stops: Lessons from Australia and Chile - Ricardo J. Caballero; Kevin Cowan; Jonathan Kearns (Inter-American Development Bank, Research Department, 2005)
Latin American economies are exposed to substantial external vulnerability. Domestic imbalances and terms of trade shocks are often exacerbated by sudden financial distress. This paper explores ways of overcoming external vulnerability, drawing lessons from a detailed comparison of the response of Chile and Australia to recent external shocks and from Australia`s historical experience. It is argued that, in order to understand sudden stops and the mechanisms to smooth them, it is useful to highlight and then draw a distinction between two dimensions of investor confidence: country-trust and currency-trust. While these two dimensions are interrelated, there are important distinctions. Lack of country-trust is a more fundamental and serious problem behind sudden stops. But lack of currency-trust may be a source of country-trust problems as well as weaken a country`s ability to deal with sudden stops. The paper further discusses steps to improve investor confidence in the medium run along these two dimensions, as well as policies to reduce the impact of country-trust and currency-trust weaknesses in the short run.
Keywords: 330; Kapitalimport; Kapitalmobilität; Terms of Trade; Schock; Außenwirtschaftliches Gleichgewicht; Anlageverhalten; Vertrauen; Vergleich; Chile; Australien; Finanzkrise